Channels of R&D spillovers an empirical investigation of Swiss firms - Harabi, Najib
Research and development (R&D) spillovers are, potentially, a major source of endogenous growth in various recent 'new growth theory' models. According to these models, firms engage in R&D in order to seek rents. Public aspects of this R&D then spill over to other firms, thereby creating increasing returns relating to scale and long-term growth. The actual mechanism by which spillovers occur has, however, not been systematically studied. In order to provide empirical facts on this issue the paper investigates the effectiveness of various channels of R&D spillovers. The analysis is based on a survey conducted among 358 Swiss R&D executives representing 127 different lines of business, mainly in the manufacturing sector. The results can be summarized as follows. First, undertaking independent R&D was perceived by the R&D executives questioned as the most effective channel of R&D spillovers at the intra-industry level. This was followed by reverse engineering for product innovations and the utilization of publications and information from technical meetings for process innovations. Second, learning methods that rely on interpersonal communication were judged as moderately effective in the following order of importance : (i) publications and technical meetings; (ii) conversations with employees from innovating firms; and (iii) hiring away employees from innovating firms. The last method, especially, is not valued as effective in the Swiss context. Third, learning methods related to the patent system-licensing technology and patent disclosures in the patent office-were seen as moderately effective or not effective at all. Fourth, the effectiveness of the various channels of R&D spillovers varies from one industry to another. Fifth, the various channels of R&D spillovers can be reduced to subgroups, so that patterns of learning of competitive technology can be established.
In the past little systematic research has been conducted into R&D spillovers. The author bases his analysis on 358 R&D executives covering 127 lines of business.
Keywords: R&D.